(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
As a result of the expedition to the Mezynskyi National Nature Park (Chernihiv Region, Ukraine), 259 species of fungi-like protists and fungi were recorded, among which 235 are new to the park. Among new records, four species belong to Myxomycota, one to Zygomycota, 128 to Ascomycota, and 102 to Basidiomycota. 14 species, namely Capronia pulcherrima, Flammocladiella anomiae, Garnaudia elegans, Hypomyces corticiicola, Mollisia caespiticia, Neodidymelliopsis negundinis, Nigrograna fuscidula, Parafenestella germanica, Phaeobotryon negundinis, Skeletocutis nemoralis, Stylonectria wegeliniana, Trichoderma atrobrunneum, T. protopulvinatum and Xylomelasma sordida, are new to Ukraine. The most of recorded species are fungicolous. Found Exidiopsis sp. is probably an undescribed, new to science species that belong to the E. effusa complex. Among the species already known in Ukraine, the rarest are Acanthostigmella pallida, Anomalemma epochnii, Arachnocrea stipata, Bactrodesmium leptopus, Fusicolla epistroma, Hilberina caudata, Hydnocristella himantia, Neocucurbitaria rhamni, Nitschkia grevillii, Peniophora rufa, Pezicula corticola, Polycephalomyces tomentosus, Rigidoporus crocatus, Selenosporella gliocladioides, Spadicoides grovei, Sporophagomyces chrysostomus, Taeniolella delicata and Tripospermum camelopardus. A brief historical overview of the mycological studies in the park allows to combine the literature data and our own findings, thus producing the general checklist of the fungal species of the Mezynskyi National Nature Park. This list currently includes 509 species. Among them, there are 25 species of Eumycetozoa, one of Mucoromycota, 215 of Basidiomycota, and 268 of Ascomycota. In comparison with the information about other nature reserves of Ukraine, it becomes obvious that further studies of the mycobiota in the Mezynskyi Park are needed.